Honey bee death from aerosols inadvertently produced from propelled aerial dispersal of a solid ant bait. Issue 12 (26th September 2022) - Hoffmann, Benjamin D.; Quinn, Greg
Abstract: Background: Hydrogels are a new bait form, and multiple studies have found minimal potential or actual nontarget impacts associated with their use. However, in 2020, aerial applications of hydrogels containing fipronil unequivocally resulted in honey bee deaths. Here we detail four studies that then were conducted to determine how the bees were exposed to the active constituent and how to modify the aerial treatment protocols to eliminate the risk to bees. Results: The first trial confirmed the existence of fipronil in aerosol form. The second trial quantified that in specific wind conditions the aerosols were falling to the ground at a maximum distance determined by an approximate 30° angle from the ground to the dispersal point, and that free‐falling hydrogels either do not produce aerosols or, if so, at volumes too negligible to be collected or quantified. The third trial confirmed that even bee hives upwind and several hundreds of metres away from the area being baited can be contaminated by the aerosols. The fourth trial found no bee hive mortality as a result of either free‐falling bait or moving bee hives 500 m beyond the treatment area. Conclusion: The aerosol issue is likely to occur with every motorized mechanism dispersing hydrogels. It is possible that the same issue happens with solid dry products if they produce a fine dust when propelled during dispersal. Further research into this issue is warranted. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Aerial applications of hydrogels containing fipronil unequivocally resulted in honey bee deaths. We confirmed that aerosols were being produced when the product was propelled for dispersal. It is possible that the same issue happens with solid dry products if they produce a fine dust when propelled during dispersal.